Combination of verteporfin-photodynamic therapy with 5-aza-2’-deoxycytidine enhances the anti-tumour immune response in triple negative breast cancer - Banerjee, Shramana M.; Acedo, Pilar; El Sheikh, Soha; Harati, Rania; Meecham, Amelia; Williams, Norman R.; Gerard, Gareth; Keshtgar, Mohammed R. S.; MacRobert, Alexander J.; Hamoudi, Rifat (Frontiers in Immunology, 2023)
Triple negative breast cancer (TNBC) is a subtype of breast cancer characterised by its high tumourigenic, invasive, and immunosuppressive nature. Photodynamic therapy (PDT) is a focal therapy that uses light to activate a photosensitizing agent and induce a cytotoxic effect. 5-aza-2'deoxycytidine (5-ADC) is a clinically approved immunomodulatory chemotherapy agent. The mechanism of the combination therapy using PDT and 5-ADC in evoking an anti-tumour response is not fully understood. The present study examined whether single dose of 5-ADC enhances the cytotoxic and anti-tumour immune effect of low dose PDT with verteporfin as the photosensitiser in TNBC orthotopic syngeneic murine model, using the triple negative murine mammary tumour cell line 4T1.Functional experiments showed that PDT was most effective when used in combination with 5-ADC to optimize its efficacy. 5-ADC/PDT combination therapy elicited a synergistic effect in vitro and was significantly more cytotoxic than monotherapies on 4T1 tumour cells. For tumour therapy, all types of treatments demonstrated histopathologically defined margins of necrosis, increased T cell expression in the spleen with absence of metastases or distant tissue destruction. Flow cytometry and digital pathology results showed significant increases in CD8 expressing cells with all treatments, whereas only the 5ADC/PDT combination therapy showed increase in CD4 expression.Bioinformatics analysis of in silico publicly available TNBC data identified BCL3 and BCL2 as well as the following anti-tumour immune response biomarkers as significantly altered, indicating increase in anti-tumour response following treatment, in TNBC compared to other breast cancer subtypes: GZMA, PRF1, CXCL1, CCL2, CCL4, and CCL5. The results showed concomitant increase in BCL3, with decrease in BCL2 expression in TNBC treatment as well decrease in PRF1, CCL2, CCL4, and CCL5 genes with 5-ADC and 5-ADC/PDT treatment in both spleen and breast tissue, with the latter showing the most decrease.To our knowledge, this is the first study showing the innate and adaptive immune biomarkers are activated during PDT related treatment of the TNBC 4T1 mouse models. The results also indicate that some of the immune response biomarkers can be used to monitor the effectiveness of PDT treatment in TNBC murine model warranting further investigation in human subjects.